2016
DOI: 10.14393/bj-v32n2a2016-30162
|View full text |Cite
|
Sign up to set email alerts
|

Enamel loss and superficial aspect during bonding and debonding of metallic brackets

Abstract: ABSTRACT:To evaluate the cumulative enamel loss during bonding and debonding procedures of orthodontic metallic brackets and to analyze the enamel superficial roughness. Forty-seven maxillary first premolars were obtained for quantitative and qualitative analysis. For quantitative analysis, forty premolars were weighed at each stage of treatment and the equivalent thickness of enamel loss was measured. The amount of tooth mass loss in each stage was divided by the density value to obtain the corresponding enam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
2
1
0
6
Order By: Relevance
“…Here, enamel conditioning with 37% phosphoric acid caused enamel loss of 6 to 12μm. These results are similar to study conducted by Ferreira EF et al 21 who reported variations in enamel loss of about 4 to 17μm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, enamel conditioning with 37% phosphoric acid caused enamel loss of 6 to 12μm. These results are similar to study conducted by Ferreira EF et al 21 who reported variations in enamel loss of about 4 to 17μm.…”
Section: Discussionsupporting
confidence: 92%
“…Forces applied to base of the bracket and to adhesive created stress concentration regions within the enamel that caused separation at the adhesive-enamel interface. Studies by Ferreira EF et al 21 and Retief DH and Denys FR [22] found similar results. OCT images showed residual adhesive resin irregularly adhered on the enamel surface after de-bonding of metallic bracket.…”
Section: Discussionsupporting
confidence: 62%
“…A remoção de remanescentes resinosos da superfície dentária com o uso de instrumentos rotatórios, após o tratamento ortodôntico, podem, eventualmente, causar danos ao esmalte (2,6,9,11,13,15) e perda de estrutura superficial com exposição das terminações do prisma do esmalte para o ambiente bucal, acúmulo de placa bacteriana e pigmentos nas microfissuras, podendo causar uma diminuição da resistência superficial aos ácidos orgânicos e isso, eventualmente, torna o esmalte mais propenso à desmineralização e resulta em manchas na interface resina/esmalte (1,2,6,9,12,14,(16)(17)(18), podendo acarretar risco de danos irreversíveis ao esmalte (3,8,10,19). Por isso, é preciso considerar a importância de se tentar, após a remoção da resina residual do esmalte, restaurar a superfície tão próxima quanto possível das condições do pré-tratamento (9), apesar de nenhuma superfície do esmalte ter sido restaurada ao seu aspecto original (19). A hipótese de que o uso de brocas para a remoção da resina residual agride e altera a superfície do esmalte se confirmou neste estudo.…”
Section: Discussionunclassified
“…Embora não tenha observado consenso na literatura, a forma mais comum de remover resíduos de adesivo, após a remoção ortodôntica, é por meio de brocas de carbeto de tungstênio (1), sendo que esta opção foi sugerida por diversos autores (7,16,(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionunclassified
“…Although the present study has focused on issues related to diagnosis and treatment planning, it should be remembered that orthodontic treatment itself also brings with it undesirable side effects, such as tooth enamel wear and patient hygiene difficulties. 45 , 46 Ways to control them, even in the details of each procedure, can help the clinician beware of possible litigation.…”
Section: Discussionmentioning
confidence: 99%